The blind spot of consciousness - Tudor Cosma Purnavel (Meta: Research in Hermeneutics, Phenomenology and Practical Philosophy, 2013)
Délia Popa, Apparence et Réalité. Phénoménologie et psychologie de l'imagination, Hildesheim, Zürich, New York: Georg Olms Verlag, 2012, 374 p.